A Career Crafting Training Program: Results of an Intervention Study - van Leeuwen, Evelien H.; Taris, Toon W.; van den Heuvel, Machteld; Knies, Eva; van Rensen, Elizabeth L. J.; Lammers, Jan-Willem J. (Frontiers in Psychology, 2021)
This intervention study examined the effects of a career crafting training on physicians' perceptions of their job crafting behaviors, career self-management, and employability. A total of 154 physicians working in two hospitals in a large Dutch city were randomly assigned to a waitlist control group or an intervention group. Physicians in the intervention group received an accredited training on career crafting, including a mix of theory, self-reflection, and exercises. Participants developed four career crafting goals during the training, to work on in the subsequent weeks, after which a coaching conversation took place over the phone. Physicians in the control group received no intervention. A pre- and post-test 8 weeks later measured changes in job crafting and career self-management (primary outcomes) and employability (secondary outcome) of 103 physicians that completed the pre- and post-test. RM ANOVAs showed that the intervention enhanced perceptions of career self-management and job crafting behavior to decrease hindering job demands. No support was found for the effect of the intervention on other types of job crafting and employability. This study offers novel insights into how career crafting can be enhanced through training, as this is the first empirical study to examine a career crafting intervention. HR managers can use the outcomes to develop tailored career policies and career development practices.